(untitled) (Revista Electrónica REDINE, 2024)
The development of motor skills has been a source of research because it is the essence of teaching-learning in the Physical Education class and in the case in question, on the basic fundamentals of football; among the problems that arise is the relation to conditional speed capacity, how they are integrated into a single process. Therefore, an exploratory field study was carried out with a quantitative approach, the objective is to implement a teaching-learning strategy of the technical fundamentals of football in relation to the development of the speed of the players of the under 15 preselection of the Fiscal Educational Unit Twenty-Third of October. An intentional population-type sample of 65 students from the football pre-selection was taken, 37 are male and 27 female, within the methods applied are those of analytical-synthetic, historical-logical, inductive-deductive theoretical level, on the other hand those of The empirical level was approached from the application of three specific tests for general speed and in football that were applied before during the execution of a proposal for football teaching and learning strategies and afterwards. This execution made it possible to show that by applying teaching and learning strategies related to the technical foundations of football through the integration of a series of varied exercises, they helped the development of speed in a significant way, which indicates that the strategies were relevant for the study as seen in the results.